Perlindungan Hukum Pemegang Hak Milik atas Tanah terhadap Sertifikat Tanah Miliknya - Yenti Hutapea; Meiske M. Wenseslas Lasut; Agustien Cherly Wereh (Jurnal Social Science, 2023)
This study aims to find out how to obtain land ownership rights and how to protect the law on land certificates for holders of land rights. The method used in this research is the type of normative research or better known as library research by examining existing library materials according to the problem and the sources of data obtained for this research through primary, secondary, and tertiary legal materials. The results of the research and discussion conducted indicate that in obtaining ownership rights to land, you must first register the land at the land office. Government Regulations Number 10 of 1961 and Number 24 of 1997 have provided legal protection for land certificates for holders of land ownership rights who have registered their land.